Placobdella costata (Fr. Müller, 1846) (Hirudinea: Glossiphoniidae), a leech species new for Slovenia - Vamberger, Melita (Natura Sloveniae, 2007)
The glossiphoniid leech Placobdella costata was confirmed in 2006 for the first time in Slovenia at a complex of fsh ponds named 'Draga pri Igu' some 10km south of Ljubljana (Central Slovenia). Up to 15 leeches were found attached to European pond turtles (Emys orbicularis), the main host species.
Keywords: pijavke; Slovenia; Slovenija; zoologija; zoology